All Aboard: The Effects of Port Development - César Ducruet; Réka Juhász; Dávid Krisztián Nagy; Claudia Steinwender (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines the effects of port development on the economy. By using scarce local land intensively, ports put pressure on local land prices and crowd out other forms of economic activity. We use the introduction of containerized shipping – a technology that substantially increased land requirements at the port – to estimate the effects of port development. We find an important role for the crowding-out effect both at the local and at the aggregate level. First, we show that the causal effect of the shipping boom caused by containerization on local population is zero – port development increases city population by making a location more attractive for firms and consumers, but this well-known market access effect is fully offset by the crowding-out mechanism. Second, to measure the aggregate implications, we add endogenous port development to a standard quantitative model of cross-city trade. Through the lens of this model, we estimate that containerization increased aggregate world welfare by 3.95%. However, relative to the positive welfare effects of a trade-cost reduction in standard models, our model implies a sizeable welfare cost associated with the increased land-usage of ports, partly offset by welfare gains from endogenous specialization based on comparative advantage across port- and non-port activities. In terms of the distributional effects, we find that initially poorer countries gained more from containerization as they had a comparative advantage in port development.
Keywords: O33; F60; 330; port development; containerization; quantitative economic geography